Noises Off (2006)
Colour Janet O'Reilly (director), Katherine Elliott (producer), Clar Doyle & Margie Moore (designers), Dawn Mason (stage manager). Cast: Angela Record, George Robertson, Darrel Brenton, Jackie French, Madline Holden, Ernst Rollmann, Jill Kennedy, Beothuck Street Players